Estrategias Utilizadas Para El Sostenimiento De Mi Pymes En La Industria Textil Del Sector La Alquería En Bogotá Durante La Pandemia (2022)
Companies over time have had great challenges to face, one of them is the pandemic generated by covid-19, the quarantine began in March, each business closed its doors and as a result they could not profit in a physical space in these months, which caused people to look for alternatives to profit, in the month of September (in Bogotá) physical businesses were allowed to open but with certain parameters to be met as a result of covid-19.